Spitzer Photometry of WISE-selected Brown Dwarf and Hyper-luminous Infrared Galaxy Candidates - Griffith, Roger L. (2012)
We present Spitzer 3.6 and 4.5 μm photometry and positions for a sample of 1510 brown dwarf candidates identified by the Wide-field Infrared Survey Explorer (WISE) all-sky survey. Of these, 166 have been spectroscopically classified as objects with spectral types M(1), L(7), T(146), and Y(12). Sixteen other objects are non-(sub)stellar in nature. The remainder are most likely distant L and T dwarfs lacking spectroscopic verification, other Y dwarf candidates still awaiting follow-up, and assorted other objects whose Spitzer photometry reveals them to be background sources. We present a catalog of Spitzer photometry for all astrophysical sources identified in these fields and use this catalog to identify seven fainter (4.5 μm ~ 17.0 mag) brown dwarf candidates, which are possibly wide-field companions to the original WISE sources. To test this hypothesis, we use a sample of 919 Spitzer observations around WISE-selected high-redshift hyper-luminous infrared galaxy candidates. For this control sample, we find another six brown dwarf candidates, suggesting that the seven companion candidates are not physically associated. In fact, only one of these seven Spitzer brown dwarf candidates has a photometric distance estimate consistent with being a companion to the WISE brown dwarf candidate. Other than this, there is no evidence for any widely separated (>20 AU) ultra-cool binaries. As an adjunct to this paper, we make available a source catalog of ~7.33 × 105 objects detected in all of these Spitzer follow-up fields for use by the astronomical community. The complete catalog includes the Spitzer 3.6 and 4.5 μm photometry, along with positionally matched B and R photometry from USNO-B; J, H, and Ks photometry from Two Micron All-Sky Survey; and W1, W2, W3, and W4 photometry from the WISE all-sky catalog.